Thin Ga(Sb,P)/GaP quantum wells with indirect band gap: Crystal structure, energy spectrum, exciton recombination and spin dynamics - Shamirzaev, T.S.; Yakovlev, D.R.; Kudlacik, D.; Harkort, C.; Putyato, M.A.; Gutakovskii, A.K.; Bayer, M. (Journal of luminescence, 2025)
Heterostructures with thin GaSb layers embedded in a GaP matrix are studied by transmission electron microscopy as well as steady-state and transient photoluminescence. For a single, one monolayer thick deposition with subsequent overgrowth, nonmonotonic Sb segregation results in self-organized Ga(Sb,P) double-quantum well (QW) formation. One QW is positioned deep in GaP at the designated place according to the heterostructure design, and the other QW is in the near surface region after 40 monolayers of GaP overgrowth. Both QWs are characterized by an indirect band gap. The band alignment in the QWs is identified as type I. In spite of the long (up to milliseconds) exciton lifetimes in the QWs in combination with the electron g factor of +2, the emission of the QWs demonstrates a low circular polarization degree in longitudinal magnetic fields as strong as 10 T. We demonstrate that the electron spin polarization in the Ga(Sb,P)/GaP heterostructure subject to a magnetic field occurs in the GaP layer, and spin-polarized charge carriers captured in the QWs store their spin orientation up to the millisecond time range, indicating very long spin relaxation times for the strongly localized electrons in the Ga(Sb,P)/GaP QWs. •Unusual non-monotonic antimony segregation results in the formation of two Ga(Sb,P)/GaP QWs after deposition of only one monolayer of Sb atoms.•Magnetic-field-induced circular polarization dynamics differs very in this system from previously studied indirect-band-gap QWs.•Spin-polarized charge carriers, captured into the QWs from matrix, keep their polarization for milliseconds.